1996
DOI: 10.1152/ajplung.1996.271.6.l880
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor induces expression of the PDGF receptor-alpha on human bronchial smooth muscle cells

Abstract: Bronchial smooth muscle cell (SMC) hyperplasia is a key feature in the pathology of asthma. Platelet-derived growth factor (PDGF) isoforms are SMC mitogens. We investigated the effect of basic fibroblast growth factor (bFGF), transforming growth factor-beta 1 (TGF-beta 1), interleukin-1 beta (IL-1 beta), and tumor necrosis factor-alpha (TNF-alpha) on the PDGF receptor system on human bronchial SMC from three different donors. bFGF induced gene expression of the PDGF alpha-receptor (PDGF-R alpha) approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 0 publications
0
30
0
2
Order By: Relevance
“…38,40,53,54 Results presented in other studies show that PDGF-R␣ has an intrinsic ability to initiate negative signals, 39,41,55 but a direct inhibitory effect of PDGF-R␣ on growth factor and FCS activity has never been tested. In this regard it is noteworthy that bFGF is known to up-regulate PDGF-R␣ expression in smooth muscle cells 56,57 and that patch mice-ie, PDGF-R␣ knock-out mice-present severe alterations in the cardiovascular system. 58 Therefore, we hypothesized that PDGF-BB may play a negative modulating role in ECs, inhibiting the pro-angiogenic activity of bFGF, through PDGF-R␣ signaling.…”
Section: Discussionmentioning
confidence: 99%
“…38,40,53,54 Results presented in other studies show that PDGF-R␣ has an intrinsic ability to initiate negative signals, 39,41,55 but a direct inhibitory effect of PDGF-R␣ on growth factor and FCS activity has never been tested. In this regard it is noteworthy that bFGF is known to up-regulate PDGF-R␣ expression in smooth muscle cells 56,57 and that patch mice-ie, PDGF-R␣ knock-out mice-present severe alterations in the cardiovascular system. 58 Therefore, we hypothesized that PDGF-BB may play a negative modulating role in ECs, inhibiting the pro-angiogenic activity of bFGF, through PDGF-R␣ signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Various diverse stimuli have now been demonstrated to increase the proliferation of airway smooth muscle cells in cell culture, and have been reviewed in detail elsewhere [13,47,48]. Broadly, the substances now implicated in mitogenesis of airway smooth muscle, in addition to the action of serum itself (discussed in [49]), include pro-inflammatory mediators (histamine [46], 5-hydroxytryptamine (5-HT) [50], phenylephrine [51], tachykinins [52], endothelin (ET)-1 [53±56] and leukotriene D 4 [57]), several inflammatory cell-and plasma-derived enzymes (a-thrombin [58], tryptase [59], b-hexosaminidase and b-glucuronidase [60]), polypeptide growth factors (platelet-derived growth factor (PDGF) [61], epidermal growth factor (EGF) [62], fibroblast growth factor-2 (FGF-2) [63] and insulin-like growth factors (IGFs) [64]) and thromboxanes [65]. Pro-inflammatory cytokines (interleukin-1b [66], interleukin-6 [67], and tumour necrosis factor-a [68]) also induce a proliferative response in airway smooth muscle, which is revealed only under conditions of cyclo-oxygenase inhibition [69], in which the production and action of inhibitory prostanoids such as prostaglandin E 2 is limited.…”
Section: Mediators Of Airway Smooth Muscle Proliferationmentioning
confidence: 99%
“…Several factors have been identified that may aid the phenotypic switch of airway SMCs, including platelet-derived growth factor (PDGF), epidermal growth factor, and basic fibroblast growth factor (2,3), and these factors have been shown to be elevated in the plasma of patients with asthma (4,5). Importantly, growth arrest of the proliferative/synthetic SMCs in culture restores the cells to a contractile phenotype (3).…”
mentioning
confidence: 99%